Distinguishing the glycan isomers 2,3-sialyllactose and 2,6-sialyllactose by voltammetry after modification with osmium(VI) complexes - Trefulka, Mojmír; Černocká, Hana; Fojt, Lukáš; Paleček, Emil; Ostatná, Veronika (Analytica chimica acta, 2019)
Altered glycosylation is a universal feature of cancer cells and certain glycans are well-known markers of tumor progression. In this work we studied two glycan isomers, 2,3-sialyllactose (3-SL) and 2,6-sialyllactose (6-SL), frequently appearing in glycoproteins connected with cancer. A combination of square wave voltammetry and glycan modification with osmium(VI) N,N,N',N'-tetramethylethylenediamine (Os(VI)tem) allowed to distinguish between these regioisomers, since the 6-SL molecule can bind three Os(VI), while the 3-SL only two Os(VI) moieties, as experiments using capillary electrophoresis, inductively coupled plasma mass spectrometry and thin layer chromatography showed. A similar pattern of Os(VI)-modification was found for isomers of sialyl-N-acetyllactosamine and sialylgalactose. Covalent adducts of Os(VI)tem with glycans yielded three reduction voltammetric peaks. The ratio of peak I/peak II heights depends on the content of individual regioisomer in the sample. Our proposed approach allows the determination of isomer percentage representation in the mixture after one voltammogram recording. These results show a new appropriate method for the discrimination of glycan isomers containing terminal sialic acid important for distinguishing between cancerous and non-cancerous origin of biomarkers.
Keywords: Osmium; laktosa; Square wave voltammetry; Lactose; Osmium(VI) complexes; Glycan isomers; kyseliny sialové; komplexní sloučeniny; Mercury electrodes; Sialic Acids; Electrochemical Techniques; elektrochemické techniky; Coordination Complexes; Chemical modification of carbohydrates; stereoizomerie; lidé; Humans; osmium; Stereoisomerism